PENGARUH PERTUMBUHAN EKONOMI, INVESTASI DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP KETIMPANGAN DISTRIBUSI PENDAPATAN DI INDONESIA - Annisa Febriyani; Ali Anis (Universitas Negeri Padang, 2021)
This study examines the impact of economic growth, investment and human development index on the inequality of income distribution in Indonesiafrom 2007-2016. The results of the study using panel data regression showed that: 1) Economic growth has a negative and insignificant effect on the inequality of income distribution in Indonesia with a significant of 0.2926; (2) Investment has a positive and significant effect on the inequality of income distribution in Indonesia with a significant amount of 0.0000; (3) The Human Development Index has a positive and insignificant effect on the inequality of income distribution in Indonesia with a significant amount of 0.2260; Based on the results of the joint test of the effect of the independent variables on the dependent variable, the results obtained that together the variables of economic growth, investment and human development index have a significant effect on the inequality of income distribution in Indonesia by 10%.